Active infrared motion detector for house security system - Abd. Rani, Mior Mohammad Hafiizh (2007)
Nowadays, house security system becomes the best solution to overcome house intrusion problem when user is not in house. As we know, there are many types of house security system which is too expensive and difficult to use. For that reason, an effective house security system at low cost is built where user can also program the security system by their own. This project is focusing on developing a house security system with an active infrared motion detector which is controlled by microcontroller Intel 8051. The overall project is divided into two parts. The first part is concern on the hardware development where all electronics component are connected via the circuit design using wrapping technique. An active infrared, the magnetic sensor, and keypad are the input components while buzzer, indicator, and LCD display are the output components where it’s all controlled by controller circuit. The second part is base on software programming to operate the hardware structure. Program for security system based on microcontroller Intel 8051 assembly languageis assemble using ASM51 assembler to get the binary file thus, to load into external memory of the hardware structure via serial communication. The process of downloading and executing the program is done using HyperTerminal’s communication software to the microcontroller serial port. In order to achieve the best house security system, more detectors or sensors can be connected to the microcontroller output port where it can be reprogram by user using their personal computer at home. As the result, the infrared motion detector is capable to detect motion while the microcontroller is capable to control the whole operation of the security system.